Enhancing Remote Laboratory Learning Outcomes Through Lesson Plan Integration within a Learning Management System Framework : Final Report. - Lowe, David; Bharathy, Gnana; Stumpers, Benjamin; Murray, Steve (Office for Learning and Teaching, 2014)
Over the last decade remote laboratories have emerged as valuable educational resources, providing the potential for improved educational outcomes, student flexibility, richer laboratory experiences, and cross-institutional resource sharing. Recent work has seen the successful establishment of a national laboratory sharing initiative. Whilst successful, the shared laboratories have been limited by a lack of a mechanism for systematically guiding students through laboratory lesson plans that aim to structure their learning. Preliminary work, carried out in conjunction with the EU-funded LiLa project, has shown the feasibility of integrating SCORM-based e- learning support with remote laboratory access. This project extends this work by creating lesson templates that capture best practice in laboratory-based learning, and then provides for automated linkages between stages of the lesson plan and the physical laboratory session. The result will be a learning tool that supports structured guidance for students in undertaking remote laboratory experiments.